IMPLEMENTASI "COOL JAPAN INITIATIVE" DALAM SEKTOR INDUSTRI KREATIF HIBURAN DI INDONESIA (2015-2019) - Nainggolan, Elisabeth (2022)
This research aims to discuss how the implementation of the Cool Japan Initiative in the entertainment industry sector using the concepts of soft power, nation branding, and cultural diplomacy in International Relations. The descriptive qualitative method using primary data sources and secondary data is the method that the author uses in this research. The author obtained primary data sources from the official website of the Japanese government associated with Cool Japan, such as the Cabinet Office, Cool Japan Fund, and METI (Ministry of Economy, Trade, and Industry) which are relevant sites related to the topic to be researched. Furthermore, when collecting secondary data sources, the authors collect data obtained from documents that have been previously processed, such as journals, books, articles, magazines, and other literary sources. The final result of this study shows that the soft power used by Japan can make Japan succeed in rebuilding the country's image from the previous era as a bad country to loving a peaceful country because Japan carried out cultural diplomacy in a good way and it had a good impact on Japan. It can be seen from the positive reaction of the global community towards the entry of Japanese culture into the country. Japan is trying to project a good image of itself through various initiatives, especially in Indonesia, which has a long history of friendship. One of the main methods of enhancing Japan's image is through the use of popular culture. Cool Japan has become a concept to communicate Japan's attractiveness to other countries and has succeeded in building a good image and enhancing bilateral relations between Japan and Indonesia. Keywords: entertainment, Cool Japan, creative industry, Japan's national interest, manga, soft power.